Analisa AC Power Automatic Switch Module dengan Metode Dual Power PLN dan Panel Surya - Sadewa, Ery; Hilal, Yusuf Nurul; Derman, Derman (Electrical Engineering, Universitas Mercu Buana, 2024)
Power outages can cause disruption of service continuity, especially in service activities in the trade, hospitality, hospital, and industrial sectors. Today the distribution of PLN's electrical energy often fails in distribution due to internal and external factors, to meet the need for continuity of electrical energy, other sources of electrical energy are needed so that if there is a power outage from PLN, consumers' needs for electrical energy are not disturbed. These sources of electrical energy are temporary to serve the electrical load in the utilization of PLN's electrical energy as the main energy source. ATS (Automatic Transfer switch) is a tool that functions to move connections between one electric voltage source and another voltage source automatically or can also be called Automatic COS (Change Over Switch), a one-phase ATS by getting more economical and easy results in maintenance. ATS in this tool can work well in the switching process manually or automatically. When PLN has an outage, there is a time delay of ± 7 seconds before the energy from the solar cell starts. This aims to keep the components from being damaged in the event of an outage.